Culture of pedagogical intercourse within the context paradigm professional competence and communication training primary school teachers (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article describes the technology of a culture of pedagogical communication of primary school teachers; defined conditions, ways, especially the formation of professional communicative competence of primary school teachers.
Keywords: communication; pedagogical communication; culture; communicative competence; language